Discovery of novel conjugates of quinoline and thiazolidinone urea as potential anti-colorectal cancer agent - Li Xiong; Huan He; Mengmeng Fan; Liping Hu; Fei Wang; Xiaomeng Song; Shengmin Shi; Baohui Qi (Journal of Enzyme Inhibition and Medicinal Chemistry)
Based on the obtained SARs, further structural optimisation of compound BC2021-104511-15i was conducted in this investigation, and totally ten novel quinoline derivates were designed, synthesised and optimised for biological activity. Among them, compound 10a displayed significant in vitro anticancer activity against COLO 205 cells with an IC50 value of 0.11 μM which was over 90-fold more potent than that of Regorafenib (IC50>10.0 μM) and Fruquintinib (IC50>10.0 μM). Furthermore, compound 10a exhibited over 90-fold selectivity towards COLO 205 relative to human normal colorectal mucosa epithelial cell FHC cells. Flow cytometry study demonstrated that compound 10a could induce apoptosis in COLO 205 cells, however, it could not induce cell cycle arrest in COLO 205 cells. The results of preliminary kinase profile study showed that compound 10a was a potential HGFR and MST1R dual inhibitor, with IC50 values of 0.11 μM and 0.045 μM, respectively.